Effect of ambient temperature on the micro-explosion characteristics of soybean oil droplet: The phenomenon of evaporation induced vapor cloud. (August 2019) - Wang, Lintao; Wang, Jigang; Qiao, Xinqi; Ju, Dehao; Lin, Zhimin
Highlights: Soybean oil droplet shows four-staged evaporation characteristics at high temperatures. The micro-explosion strength increases with the increase of ambient temperature. Evaporation induced vapor cloud was first observed at 973 K. Homogenous and heterogeneous nucleation were observed at 873 K, 923 K and 973 K. Abstract: Micro-explosion characteristics of soybean oil droplet were investigated using high speed backlight imaging technique at ambient temperature 873 K, 923 K and 973 K. Experimental results indicate that soybean oil droplet underwent transient heating phase, micro-explosion evaporation phase, equilibrium evaporation phase, and residue evaporation phase at all the studied temperatures. The evaporation rate of equilibrium evaporation phase is increased when the temperature increased. However, a decrease for the evaporation rate of residue evaporation phase. Homogeneous and heterogeneous nucleation are observed at all temperatures, homogeneous nucleation lead to strong micro-explosion and heterogeneous nucleation lead to weak micro-explosion. Moreover, micro-explosion strength increased when the ambient increased. It was found that the micro-explosion occurred at the end of droplet evaporation, this is one of the reasons for the poor atomization characteristics of bio-oil in the engine. More importantly, the evaporation induced vapor cloud is observed at 973 K, this is mainly due to the non-isothermal condensation caused by Stefan outflow.